Investigation of Various Epidemic Diseases in Some Countries by Mathematical Models SI and SIS - Cilli, A.; Ergen, K. (AMER INST PHYSICS, 2017)
In this study, efficiency of Si and SIS mathematical models were defined in the prediction of the number of infected people with malaria and Acquired Immune Deficiency Syndrome (AIDS) as infectious diseases. Afghanistan and Angola were selected for their geographical and economical features. Although the models do not predict exact numbers for each year, in a long term and in a normal conditions (unless there are external parameters such as natural disaster, war, emigration and terrorism) they can predict the trend for the diseases and can tell when to disappear. Therefore, updating data are of importance to achieve the powerful prediction.
Keywords: Physics